The 2011 Swiss Elections: Introduction. Issue 4 (29th October 2014) - Lachat, Romain; Lutz, Georg; Stadelmann‐Steffen, Isabelle
Abstract The 2011 Swiss federal elections represent a turning point in recent Swiss politics. The Swiss People's Party did not manage to increase further its vote share, after more than two decades of electoral successes. Also, the 2011 elections were characterized by the strong gains of two relatively new centrist parties, the Green Liberal Party and the Conservative Democratic Party. This election thus marks an end of the trend towards a growing level of party polarization. The introduction to this special issue puts these recent developments in context, discusses some of its consequences, and highlights how the articles in this special issue shed light on understanding the voting behaviour in Switzerland.